COMPARISON OF PROPERTIES OF BITUMINOUS BINDERS AFTER AGING BY DIFFERENT METHODS - Andrey Galkin; Serhii Oksak; Yan Pyrig (Дороги і мости, 2022)
Introduction. The performance and durability of asphalt pavements are majorly conditioned by the quality of the bituminous binders. One of the main disadvantages of asphalt pavements is the permanent change in their properties in time due to the aging of the binder. Various laboratory methods of aging are used to predict the intensity of changes in the properties of bituminous binders that occur during the asphalt mixing at plants and the lifetime of asphalt concrete in the pavement.